The existing methods and protection products analysis of radio electronic equipment from the powered pulmonary electromagnetic radiation effect of ultrasonic short-term permeability - Sotnikov, A.; Yasechko, M.; Tantsiura, A.; Ochkurenko, A.; Maksiuta, D. (Національний технічний університет "Харківський політехнічний інститут", 2019)
The possibilities analysis of the implementing protection radio electronic means from the powerful pulsed electromagnetic radiation by known methods and existing devices has been carried out. It was determined that at the operation stageof the radio-electronic means the main method of protection is shielding. But the presence of technological openings, cable entry channels, defects in enclosures makes it impossible to protect radio electronic devices from powerful pulsed electromagnetic radiation of ultra short duration by this method. It has been pointed out the need to search for new technologies that will reduce or completely eliminate the penetration of electromagnetic radiation into the cascades of radio-electronic means. The concept of the radio-electronic protection means at their use stage is formulated on the basis of nature-like absorption technologies, reflection and removal ofthe powerful pulsed electro absorbing and locking properties of the protective equipment. Nature-like technologies have the advantage of an instantaneous response of the state of the electronic subsystem to the effects of electromagnetic radiation and, accordingly, an instantaneous change in the electro physical properties of the solid-state ionized air environment. Thus, an instant change occurs in the reflective, absorbing and locking properties of the protective equipment. Also, such technologies retaintheir performance throughout the entire electronic means life cycle and have the ability to withstand pulsed overload.

Проведено аналіз можливостей реалізації захисту радіоелектронних засобів від потужного імпульсного електромагнітного випромінювання відомими способами і існуючими пристроями. Встановлено, що на етапі експлуатації радіоелектронних засобів основним методом захисту є екранування. Але наявність технологічних отворів, каналів кабельного вводу, дефектів в корпусах унеможливлює захист радіоелектронного пристрою від потужного імпульсного електромагнітного випромінювання ультракороткої тривалості. Відмічена необхідність пошуку нових технологій, які дозволять зменшити або повністю виключити проникнення електромагнітного випромінювання в каскади радіоелектронних засобів. Концепція засобів радіоелектронного захисту на стадії їх використання сформульована на основі природоподібних технологій поглинання, відбиття і відведення потужного імпульсного електромагнітного випромінювання за рахунок використання електроабсорбуючих і замикаючих властивостей захисного обладнання. Природоподібні технології мають перевагу миттєвого відгуку стану електронної підсистеми на вплив електромагнітного випромінювання і, відповідно, миттєвої зміни електрофізичних властивостей твердотільного іонізованого середовища. Таким чином, відбувається миттєва зміна відбиваючих, поглинаючих і замикаючих властивостей захисного обладнання. Крім того, такі технології зберігають свої характеристики протягом усього життєвого циклу електронних засобів і здатні витримувати імпульсні перевантаження.
Аналіз існуючих методів і пристроїв захисту радіоелектронних засобів від впливу потужногоімпульсного електромагнітного випромінювання ультракороткої тривалості
Keywords: solid-state plasma medium; gaseous plasma medium; radioisotope technology; твердотільне плазмове середовище; газоподібне плазмове середовище; радіоізотопна технологія